SYSTEMATIC LITERATURE REVIEW: POLA PIKIR ORANG TUA DAN STUNTING - Jim Briand Kolianan; Jeni M. Ataupah (Jurnal Pluralis, 2024)
This research aims to determine the influence of parents' mindset on stunting. This research uses the SLR (Systematic Literature Review) method. Data sources were obtained from articles, research journals, expert theories, and books. The variables used in this research are the independent variable and the dependent variable. From these two variables, it can be concluded that parents' mindset has a significant impact on stunting. There is a need for education about the importance of understanding stunting and its causes correctly, this will change people's mindset and parenting patterns to eliminate stunting in the future.